Boredom, Art and Work: Tehching Hsieh's 'Time Clock Piece' and the experience of working life. (September 2022) - Lawn, Katy
This paper addresses the work of Tehching Hsieh, a Taiwanese-American conceptual artist who uses boredom – and specifically boring labour – as a mode of production and conceptual influence in his artworks. The paper is introduced by sketching the connections between boredom, work and art; before considering the relationship that artworks have with production and boring labour. Particular attention is paid to the way that time-based artworks – specifically performance works – present a unique opportunity to consider boredom and labour, since they foreground the process of labour itself as art. This enables a reconsideration of the way in which work routines are often culturally coded as meaningful or essential pursuits; without proper consideration of the philosophical assumptions around work or the way that work is experienced. Through considering Hsieh's approach, this paper elucidates the ways in which boredom functions as a critique of the nature of experience offered when undertaking labour in capitalist societies. Hsieh's performance artwork 'One Year Performance 1980-81' – also known as 'Time Clock Piece' – is the substantive focus of the paper. An argument is developed around how artists replicate and critique bored time-spaces characterised by the elements of working life: namely – temporal restrictions, repetition and boring work. This leads to a closing-down of life's textures, experiences and possibilities. This in turn reflects the fact that work often cannot offer the meaning, interest and fulfilment that it promises to the working subject. Hsieh's artwork is emblematic of this void of meaning, but also paradoxically stimulates a movement towards meaning-making.